Porphyrin Bound to i‐Motifs: Intercalation versus External Groove Binding. Issue 13 (22nd June 2017) - Qin, Tingxiao; Liu, Kunhui; Song, Di; Yang, Chunfan; Su, Hongmei
Abstract: G‐rich and C‐rich DNA can fold into the tetrastranded helical structures G quadruplex or C quadruplex (i‐motif), which are considered to be specific drug targets for cancer therapy. A large number of small molecules (so‐called ligands), which can bind and modulate the stability of G quadruplex structures, have been widely examined. Much less is known, however, about the ligand binding interactions with the C quadruplex (i‐motif). By combining steady‐state measurements (UV/Vis, fluorescence, and induced circular dichroism (ICD)) with time‐resolved laser flash photolysis spectroscopy, we have studied the binding interactions of cationic porphyrin (5, 10, 15, 20‐tetrakis( N ‐methylpyridinium‐4‐yl)‐21  H, 23  H ‐porphyrin, abbreviated as TMPyP4) with i‐motifs (C3 TA2 )3 C3 T and (C4 A4 C4 )2. The intercalation binding mode through π–π stacking of the porphyrin macrocycle and the C:C + hemiprotonated base pair has been identified for the first time. The coexistent binding modes of intercalation (≈80 %) versus external major‐groove binding (≈20 %) have been determined quantitatively, thereby allowing a fuller understanding of the porphyrin–i‐motif interactions. The ionic strength was found to play an important role in affecting affects the binding modes, with the progressive increase in the ionic strength resulting in the gradual decrease in the intercalation percentage and an increase in the groove‐binding percentage. Furthermore, an extended study of the porphyrin derivative with four bulky side‐arm substituents (T4) suggests a complete prohibition of the intercalation mode owing to large steric hindrance, thereby providing a novel groove‐binding ligand with site selectivity. These results provide in‐depth mechanistic insights to better understand the ligand interactions with i‐motifs and guidance for related applications in anticancer drug design. Abstract : Bound for greatness : The intercalation binding mode through the π–π stacking of the porphyrin macrocycle and the C:C + hemiprotonated base pair has been identified for the first time (see figure). The coexistent binding modes of intercalation versus external major‐groove binding were determined quantitatively to further understand the porphyrin–i‐motif interactions.